1984
DOI: 10.1002/bscb.19840930608
|View full text |Cite
|
Sign up to set email alerts
|

NMR Studies on Imidines. VI.1H and 13C Nuclear Magnetic Resonance Study on the Tautomerism of Phthalic Imidine.

Abstract: Phthalic imidine is shown to be present in DMSO-d6 solution as a 5 : l mixture of 3-amino-1~-isoindol-l-imine (9) and 1,3-diiminoisoindoline (fi) by The amino tautomer 9 also predominates in other solvents: CDC13,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Since the peak was shifted to downfield, we consider that then new‐produced methine may be adjacent to an electron‐withdrawing group. Combined with the previous results, it can be inferred to be adjacent to isoindoline moiety in this system . In addition, the peak at 2.18 ppm is probably due to the chemical shift of the residual methylene in the alicyclic groups due to the change of the chemical environment .…”
Section: Resultssupporting
confidence: 78%
“…Since the peak was shifted to downfield, we consider that then new‐produced methine may be adjacent to an electron‐withdrawing group. Combined with the previous results, it can be inferred to be adjacent to isoindoline moiety in this system . In addition, the peak at 2.18 ppm is probably due to the chemical shift of the residual methylene in the alicyclic groups due to the change of the chemical environment .…”
Section: Resultssupporting
confidence: 78%
“…Theoretical [43,44] and X-ray diffraction [42] studies indicate that the imino form possesses lower energy and is therefore expected to be the predominant in the solution, whereas the amino form is prevalent in the solid state because of the intermolecular hydrogen bond that is formed. On the other hand, NMR spectroscopic studies [45] show that phthalimidine exists in [D 6 ]DMSO solution as a 5:1 mixture of the amino and imino forms. For 6-9, the reaction mixtures rapidly (in ca.…”
Section: Resultsmentioning
confidence: 98%
“…A detailed ' H and 13C NMR study (7) has revealed that the parent compound 1 exists in DMSO-d6 solution as a 5:l tautomeric mixture in which the amino form J&i predominates.…”
Section: Introductionmentioning
confidence: 99%